Laryngeal Preservation Approaches: Considerations for New Selection Criteria Based on the DeLOS-II Trial - Dietz, Andreas; Wiegand, Susanne; Kuhnt, Thomas; Wichmann, Gunnar (Frontiers in Oncology, 2019)
In the locoregionally advanced group of larynx and hypopharyngeal squamous cell carcinomas (LHSCC), there are two kinds of patients: those who are candidates for functional larynx organ preservation (LP) by avoiding ablative surgery and those who are not. Currently, the distinction is depending on the patient’s needs and desires, the experience and recommendation of the surgeon, the philosophy of the institution and others. The key note VA trial established non-surgical LP in advanced LHSCC utilizing induction-chemotherapy (IC) with PF (cisplatin, P plus 5-fluorouracil, F) followed by irradiation (IC+RT) as appropriate alternative treatment to total laryngectomy (TL) already 25 year ago. Despite verification of this finding by the EORTC 24891 trial there is still a debate about the best protocol regarding balance between laryngectomy-free survival (LFS) with acceptable late toxicity and functional outcome and survival. Potential treatment options to preserve larynx function may be IC+RT or primary concurrent chemo-radiotherapy (CRT). Cisplatin-based CRT is still recommended as best protocol for LP in the USA. But current views on long term survival with functional organ preservation and still high failure rates are addressing the need of better selection of patients which will be discussed as follows taking the current debate in literature and in particular the recently published data of the DeLOS-II trial in consideration. The randomized phase II DeLOS-II-trial was designed as a study to the use of Taxotere-Cisplatin-5FU (TPF)-chemotherapy followed by radiotherapy with or without cetuximab (arm A TPF; arm B TPF±E) in the primary therapy of only by TL operable carcinomas of the larynx/hypopharynx. DeLOS-II introduced the empirical cut-off of ≥30% tumor surface shrinkage reduction estimated after the first cycle IC (short induction) due to endoscopic re-evaluation by the surgeon as early selector for surgical or non-surgical treatment.